2011
DOI: 10.1038/msb.2011.94
|View full text |Cite
|
Sign up to set email alerts
|

Queueing up for enzymatic processing: correlated signaling through coupled degradation

Abstract: Overloaded enzymatic processes are shown to create indirect coupling between upstream components in cellular networks. This has important implications for the design of synthetic biology devices and for our understanding of currently inexplicable links within endogenous biological systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
223
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(228 citation statements)
references
References 42 publications
5
223
0
Order By: Relevance
“…Note that the enzymatic decay of each protein depends on the concentration of both, because both AraC and LacI are targeted by the same protease (39). All parameter values are provided in the Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the enzymatic decay of each protein depends on the concentration of both, because both AraC and LacI are targeted by the same protease (39). All parameter values are provided in the Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…12 could be replicated by an enzymatic degradation in a saturated regime (see ref. 28 for a biological instance of such a mechanism). In summary, the proposed chemical equivalent to Eq.…”
Section: Biochemical Network To Implement the Ratio Test For Concentmentioning
confidence: 99%
“…Further computational studies have found that, because modules share limited amounts of transcriptional/translational resources, the expression levels of proteins in seemingly unconnected modules become surprisingly coupled [55,56] and the dynamical behavior of simple activation cascades becomes unpredictable [57]. Counter-intuitive interactions have also been experimentally observed when di↵erent modules share common enzymes, whose scarcity leads to interesting synchronized behavior [58]. All these e↵ects make a module's salient properties poorly predictable and, as a result, confound system design.…”
Section: Modularity Of Functional Modules: the E↵ects Of Resource Shamentioning
confidence: 99%